Cycloartane glycosides from Astragalus gombo. (March 2015) - Maamria, Leyla; Long, Christophe; Haba, Hamada; Lavaud, Catherine; Cannac, Audrey; Benkhaled, Mohammed
Graphical abstract: Six new cycloartane-type triterpene glycosides, along with one cycloartane triterpene glycoside and two flavonol glycosides were isolated from the aerial parts of Astragalus gombo . Highlights: We study the chemical composition of Astragalus gombo Coss. & Dur. Six new cycloartane-type glycosides are isolated and identified. This result is in good agreement with that of the previous studies made on the genus Astragalus . Abstract: Six new cycloartane-type triterpene glycosides named 3- O -[ β -d -glucopyranosyl(1 → 2)- β -d -xylopyranosyl]-3 β, 16 β, 23( R ), 24( R ), 25-pentahydroxycycloartane (1 ), 3- O -[ β -d -glucopyranosyl(1 → 2)- β -d -xylopyranosyl]-3 β, 16 β, 23( R ), 24( R )-tetrahydroxy-25-dehydrocycloartane (2 ), 3- O -[ β -d -xylopyranosyl]-6 α -acetoxy-23 α -methoxy-16 β, 23( R )-epoxy-24, 25, 26, 27-tetranorcycloartane (3 ), 3- O -[ β -d -xylopyranosyl]-6 α -acetoxy-23 α -butoxy-16 β, 23( R )-epoxy-24, 25, 26, 27-tetranorcycloartane (4 ), 3- O -[ β -d -glucopyranosyl(1 → 2)]- β -d -xylopyranosyl]-6 α -acetoxy-23 α -methoxy-16 β, 23( R )-epoxy-24, 25, 26, 27-tetranorcycloartane (5 ), 3- O -[ β -d -glucopyranosyl(1 → 2)]- β -d -xylopyranosyl]-23 α -methoxy-16 β, 23( R )-epoxy-4, 25, 26, 27-tetranorcycloartane (6 ), in addition to three known secondary metabolites consisting of another cycloartane triterpene glycoside and two flavonol glycosides, were isolated from the aerial parts of Astragalus gombo Coss. & Dur. (Fabaceae). The structures of the isolated compounds were established by spectroscopic methods, including 1D and 2D-NMR, mass spectrometry and comparison with literature data.